A Review of Physical Appearance of Molten Metal Droplet in Arc Welding Process - Saha, Avash Kumar; Majumdar, Sujit (Proceeding International Conference on Religion, Science and Education, 2022)
This fundamental research presents an overview of a molten metal flow in arc welding processes. This study presents a systematic review of the fluidity of molten drop in any surface concerning the investigation results. This paper consists of monochromatic imaging of a reflection of molten droplets, welding spectrum of a grating monochromator by high-speed imaging with a prism, reviewing of the physical mechanism of molten macro drops with implementing of hydroforming effect. Many research papers are being reviewed but a systematic review of molten droplets was missing in current research areas. However, the outcome of the study is to develop an overview structural idea of molten droplets.